Characteristics of the Anterior Segment Biometry and Corneal Endothelium in Eyes with Pseudoexfoliation Syndrome and Senile Cataract - Banu Bozkurt; Hüseyin Güzel; Ümit Kamış; Şansal Gedik; Süleyman Okudan (Türk Oftalmoloji Dergisi, 2015)
Objectives: To evaluate the anterior segment biometric features and corneal endothelial changes in eyes with pseudoexfoliation (PEX) syndrome and senile cataract. Materials and Methods: The central corneal thickness, anterior chamber depth (ACD), pupil diameter, lens thickness, endothelial cell density (ECD), and percentages of polymegathism and pleomorphism of 52 subjects with PEX and cataract were compared with 51 age- and gender-matched control subjects with cataract using optical low-coherence reflectometry (OLCR, Lenstar LS 900; Haag Streit AG, Switzerland) and in-vivo confocal microscopy (Confo Scan 4, Nidek Co. Ltd, Osaka, Japan). Nineteen subjects with PEX syndrome had glaucoma and were using anti-glaucoma medications. Only one eye of the subjects was used in statistical analysis and a p value less than 0.05 was considered statistically significant. Results: None of the OLCR parameters reached statistically significant differences among the 3 groups (ANOVA p>0.05). The percentage of eyes with ACD <2.5 mm was 13.7% in the control group, 24.2% in PEX eyes without glaucoma and 21.1% in PEX eyes with glaucoma, with no statistically significant differences (p=0.45). There was a significant difference in mean ECD among the 3 groups (ANOVA p=0.02), whereas no differences could be found in respect to polymegathism and pleomorphism (p>0.05). Mean ECD was significantly lower in the PEX glaucoma group (2,199.5±176.8 cells/mm2) than the control group (2,363±229.3 cells/mm2) (p=0.02), whereas no difference was found in mean ECD of PEX eyes without glaucoma and the control group (p=0.42). ECD was less than 2,000 cells/mm2 in 15.8% of PEX subjects with glaucoma, 9.8% of control subjects and 6.1% of PEX eyes without glaucoma, with no statistically significant difference (p=0.52). Conclusion: As eyes with both PEX glaucoma and cataract seem to be associated with decreased endothelial cell number, specular or confocal microscopy screening should be done for the patients scheduled for intraocular surgery. (Turk J Ophthalmol 2015; 45: 188-192)